Organizational health structure and measurement of higher education in Indonesia - Adiati, Rosatyani Puspita; Handoyo, Seger; Wicaksono, Dimas Aryo; Purba, Herison Pandapotan; Syarifah, Dewi (Indigenous, 2021)
The changing of governance and the increasing target of university challenge organization to maintain organizational health to support university member to achieve optimal performance. This study consisted two steps. First study was held to undertand the structure of organizational health factor, spesifically in public university setting, and involving 204 state university lecturers from 3 public universities. We used exploratory factor analysis for reducting dimensions of organizational health. It revealed that organizational health consists of four factors, which are Positive Leadership, Organizational Virtue, Positive Relationship, and Resource Support. Second study aimed to identify organizational health condition in those public universities in Indonesia using the 4 factor of organizational health that were generated in study 1. We asked 398 public university lecturers from 6 state universities to participate in study 2. We found that organizational health conditions were quite good. Further data analysis showed required improvement is needed, related to the aspects of Organizational Virtue, which indicates the ability of the organization to maintain their core activity and value, face pressure from outside and also internal people. Furthermore, Resource Support factor is also found as a factor with lowest result, it indicates there were some deficiency in facility to support organization objective.